Survey of Young People’s Sexual and Reproductive Health Knowledge in Northern Namibia - Talbot, Karine; Ruiz-Casares, Mónica (McGill Journal of Global Health, 2022)
During the first COVID-19 lockdown in Namibia (March-September 2020), there were an estimated 3,600 teenage pregnancies, an increase from the annual average of 1,400 (1). The regions of Kavango East and West were particularly impacted. In response to these figures, the Ombetja Yehinga Organisation (OYO), a youth-focused Namibian non-governmental organization, administered a survey to assess students’ sexual and reproductive health knowledge. This survey will provide baseline information regarding the effectiveness of a school-based intervention to promote safe sexual behaviours using the “Teenage Pregnancy” info-magazine. Young people completed an in-person survey which included questions relating to demographic characteristics, True or False sexual and reproductive health statements, and knowledge of contraception and school policy. Questionnaires were administered in groups after school hours by trained facilitators, checked for completeness and confidentiality using a unique identification code, scanned and shared with the team at McGill University for data entry and analysis. A total of 13 schools and 794 students aged 13-25 years participated in the survey and were included in data analysis. Knowledge on access and the safe use of contraceptives was limited, suggesting that school-based interventions (such as the OYO program) may be necessary to disseminate this crucial information.